Penerapan Ad Dhararu Yuzalu bi Mithlihi dalam Akad Penjualan Produk Berbahaya - Nurfaidah (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
The purpose of this study is to see how the application of branch rules in Islamic economic contracts. Several principles of Islamic law emphasize the importance of avoiding loss or harm for the sake of the public good. In the application of Islamic law to overcome various harms or losses, namely in the main rule "ad-dhararu yuzalu", which means "harm must be eliminated,". This rule has several more specific branches, one of which is "ad-dhararu yuzalu bi mithlihi", which means "harm must be eliminated by an equivalent harm."